Fröhlich polaron effect in flexible low-voltage organic thin-film transistors gated with high-k polymer dielectrics. (13th August 2021) - Guo, Songyang; Li, Siying; Shen, Tao; Tang, Wei; Guo, Xiaojun; Xin, Juan; Jin, Junjun; Wei, Huili; Wang, Xianbao; Li, Jinhua
Abstract: The dielectric constant of the polymer insulator layer plays a key role in the charge transport and operation voltage of organic thin-film transistors (OTFT). However, the appropriate effects have not been well distinguished yet in donor-acceptor copolymer semiconductor-based OTFT. In this work, we demonstrate that the decreased mobilities in indacenodithiophene-co-benzothiadiazole OTFTs with the increase of gate dielectric constant is due to the Fröhlich polaron effect, especially for device gated with high- k relaxor ferroelectric polymer poly(vinylidene fluoride-trifluoroethylene-chlorofloroethylene). In order to eliminate this effect, a low- k polymer is introduced as a modification layer to construct a low- k /high- k bilayer dielectric to attain better mobility and improved bias stability. Finally, flexible top-gate OTFT is demonstrated on the polyethylene terephthalate substrate, showing good bending stability even after 1000 bending tests.